Observations on Italian Bronze Age Sword Production: The Archaeological Record and Experimental Archaeology - Luca Pellegrini; Federico Scacchetti (EXARC Journal, 2014)
In spite of the very large quantity of Bronze Age swords in Northern Italy, only a few stone moulds have been found. Tests have shown that carving such big stone moulds (more than 60 cm long) requires a large amount of raw material, deep knowledge and skill, rather than a wide set of implements. It has also been shown experimentally that the long sandstone sword moulds, especially in regards to blade details, are affected by the fragility of the material, when the stone comes in contact with the flowing melted bronze. These reasons could mean that the moulds were made with other materials and through other techniques that have not left a visible (or identified?) trace on metallurgical sites, as other authors have already suggested (cfr. Ottaway and Wang 2004). A team of archaeologists and craftspeople is now working on sand casting method.